2021
DOI: 10.1093/mnras/stab1350
|View full text |Cite
|
Sign up to set email alerts
|

The shape and scatter of the galaxy main sequence for massive galaxies at cosmic noon

Abstract: We present the main sequence for all galaxies and star-forming galaxies for a sample of 28,469 massive (M⋆ ≥ 1011M⊙) galaxies at cosmic noon (1.5 < z < 3.0), uniformly selected from a 17.5 deg2 area (0.33 Gpc3 comoving volume at these redshifts). Our large sample allows for a novel approach to investigating the galaxy main sequence that has not been accessible to previous studies. We measure the main sequence in small mass bins in the SFR-M⋆ plane without assuming a functional form for the main s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 92 publications
0
11
0
Order By: Relevance
“…the density peak in the SFR-mass plane) (Renzini & Peng 2015), or using flexible Gaussian mixture models with the number of Gaussian sub-components determined by the data (Hahn et al 2019). In the limit of wide-area surveys, these data-driven approaches can accurately measure higher-order moments of the star-forming sequence such as the width or the location of the so-called 'green valley' (Sherman et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…the density peak in the SFR-mass plane) (Renzini & Peng 2015), or using flexible Gaussian mixture models with the number of Gaussian sub-components determined by the data (Hahn et al 2019). In the limit of wide-area surveys, these data-driven approaches can accurately measure higher-order moments of the star-forming sequence such as the width or the location of the so-called 'green valley' (Sherman et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the nature, evolution (both with mass and redshift), and the timescales associated with this scatter is a currently active area of research (e.g. Speagle et al 2014, Matthee & Schaye 2019, Berti et al 2021, Sherman et al 2021.…”
mentioning
confidence: 99%
“…It is not dominated by IR-bright (i.e., in dust continuum) submm galaxies (SMGs). The ALPINE galaxies are mainly located on or near the main sequence (e.g., Rodighiero et al 2011;Gruppioni et al 2013;Donnari et al 2019;Sherman et al 2021) in the SFR versus stellar mass (M star ) relation observed at these redshifts (Speagle et al 2014;Pearson et al 2018). It is mostly dominated by UVselected galaxies (see Table 1 in with about 62% of the sample identified with the dropout technique, that is LBGs and 28% that are Lyman α emitters which were selected with narrow bands.…”
Section: The Sample Of Studied Galaxiesmentioning
confidence: 99%